2005
DOI: 10.1002/pd.1312
|View full text |Cite
|
Sign up to set email alerts
|

Mild pyelectasis diagnosed by prenatal ultrasound is not a predictor of urinary tract morbidity in childhood

Abstract: Children with a mild fetal pyelectasis do not have more urinary tract morbidity during childhood than children without this finding. Therefore, there seems to be no need for additional investigation after birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 41 publications
0
6
0
3
Order By: Relevance
“…In a questionnaire-based study Damon-Elias and associates [30] investigated the clinical outcome of 146 children with mild dilatation (AP diameter 5e10 mm) at 4e9 years of age. Information on medical history was obtained from the parents of children with antenatally detected dilatation and compared with information provided by the parents of 250 age-matched normal controls.…”
Section: Mild Dilatationmentioning
confidence: 99%
“…In a questionnaire-based study Damon-Elias and associates [30] investigated the clinical outcome of 146 children with mild dilatation (AP diameter 5e10 mm) at 4e9 years of age. Information on medical history was obtained from the parents of children with antenatally detected dilatation and compared with information provided by the parents of 250 age-matched normal controls.…”
Section: Mild Dilatationmentioning
confidence: 99%
“…Other investigators have suggested that mild RPD (<10 mm) is rarely linked to significant abnormality and not predictive of urinary tract morbidity in childhood. What is interesting from our study is that despite extensive investigations, no obvious cause for the RPD was identified in 16.5% of cases.…”
Section: Discussionmentioning
confidence: 95%
“…Since the reviewed articles yielded only 79 patients with long‐term follow‐up, our data do not contribute to this discussion. However, based on data collected in our own patients, we do not perform postnatal follow‐up for PNH detected with an APD of < 10 mm30.…”
Section: Discussionmentioning
confidence: 99%
“…In Figure 2 we propose a flow diagram for a standard follow‐up protocol and adequate recording of data. This diagram is based mainly on previous work in our hospital30. Although we are aware of the fact that many clinicians will find performing a standard VCUG (and ultrasound exam) too invasive, we think that evidence supporting that opinion needs to be produced.…”
Section: Discussionmentioning
confidence: 99%